SOME BIOLOGICAL ASPECTS OF THRYSSA HAMILTONII AND THRYSSA MYSTAX IN KHOR AL-ZUBAIR, NORTHWEST ARABIAN GULF - Hussain, N A; Ali, T S (Indian Journal of Fisheries, 2011)
Study on 826 specimens of T. hamiltonii (Gray) and 439 specimens of T. mystax (Bloch and Schneider) collected from Khor al-Zubair during the period from July 1983 to June 1984 has shown that the dominant length range for both the species is 15.0-19.9 cm, representing 62.7% of the total number of T. hamiltonii and 58% of that of T. mystax. Based on GST, both species have single, prolonged spawning, extending from December to April, with peaV in March.